The Insurgent Chief - Aimard, Gustave, 1818-1883 (Salt Lake City, UT : Project Gutenberg, 2014)
"The Insurgent Chief" by Gustave Aimard is a historical novel written in the mid-19th century. Set against a backdrop of revolutionary fervor in South America, the story revolves around the characters Emile Gagnepain, a painter caught in a political web, and the noblewomen Leona and Eva de Castelmelhor, who are prisoners facing dire consequences. The plot is likely to explore themes of honor, loyalty, and the complexity of human relationships during upheaval. The opening of the story introduces San Miguel de Tucuman, where Emile, an indifferent artist, finds himself entwined in political intrigues and unexpected romantic entanglements. The narrative unfolds with the arrival of a mysterious flower thrown from a grim house, leading Emile to a letter from the Marchioness de Castelmelhor, who implores him for help. An unexpected friendship forms between Emile and Tyro, his devoted Guaraní servant, as they devise a plan to rescue the Marchioness and her daughter from impending doom, setting the stage for a gripping tale of adventure and sacrifice amidst the tumult of war. (This is an automatically generated summary.)
Release date is 2014-04-15
E-text prepared by Camille Bernard and Marc D'Hooghe (http://freeliterature.org) from page images generously made available by HathiTrust Digital Library (http://www.hathitrust.org/digital_library)
Keywords: Fiction